If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7X + 8 = 57 Reorder the terms: 8 + -7X = 57 Solving 8 + -7X = 57 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -7X = 57 + -8 Combine like terms: 8 + -8 = 0 0 + -7X = 57 + -8 -7X = 57 + -8 Combine like terms: 57 + -8 = 49 -7X = 49 Divide each side by '-7'. X = -7 Simplifying X = -7
| -4(c-10)=40 | | 68+13=-71-8x | | -2y-5=-9 | | 42=7(y+4) | | 2x-10y=16 | | 7X-7=13+3X | | 162=0.5t^2 | | 10x+25=21+14 | | 300*1=-16x | | 15=2h^2-3 | | 10x+2=7x+26 | | 6[c+4]=4c-18 | | (4a-1)(a-1)=10 | | 5x-2y=15 | | logx+log(13-x)=1 | | 3x+7=4x+28 | | 3+2b=15 | | (5-2y)4+(3y+15)3=72 | | 6x+5=9x-10 | | -159=-3+6(5x+5) | | -2(5-x)=14 | | 4(2x-10)=8(x-5) | | 5x-5(-2x-10)=-100 | | -2n+3n-6n= | | 5x-157=-4x+50 | | 72=30-6x | | 6(2x-8)=96 | | 6w+3=8w-3 | | -58=4x+6(-3+2) | | -104=7x+2(2x+14) | | x-5y+12=0 | | -2+x/7=4 |